PENGARUH KEMAMPUAN BERPIKIR KRITIS DALAM MENGANALISIS MASALAH KONSELI PADA MAHASISWA JURUSAN BIMBINGAN KONSELING IKIP PGRI BALI TAHUN 2019 - Mulyawan, I Nyoman Rajeg (LPPM IKIP PGRI Bali, 2019)
This study aims to determine students' critical thinking skills and their influence on the ability to analyze counselee problems in the implementation of individual counseling services. This research was conducted on students of the IKIP PGRI Bali counseling department. The sampling technique used is stratified simple random sampling. Data is collected by test techniques (critical thinking), rating scales (analyzing counselee problems). Data analysis used descriptive analysis and Pearson Product Moment (PPM) correlation analysis. Description of the level of critical thinking skills of students who are classified as moderate and the ability to analyze problems is also classified as moderate, there are 22%. The same number also occurred (22%) in students whose critical thinking ability was classified as moderate but the ability to analyze problems was high. The calculated results obtained by the value r is 0.752. Based on the significance level of 5%, the r table value is 0.279. Thus r count is greater than r table and it can be stated that the relationship between the independent variable (X) and the variable (Y) is significant. Based on the interpretation of the correlation coefficient r value (Riduwan, 2004), if the range of r values ??is between 0.60 - 0.799 the level of the relationship is strong.          The calculated calculated coefficient (KD) to determine the contribution of the free variable (X) to the dependent variable (Y) is 56%, this means that there are other variables (44%) that affect the dependent variable (Y). Thus it can be concluded that there is a significant relationship and the influence is categorized as strong between critical thinking skills and the ability to analyze problems in counseling for students in IKIP PGRI Bali's guidance and counseling in 2019.